For this question we need to use the formula for compound interest:
![P=P_0(1+(i)/(n))^(nt)](https://img.qammunity.org/2023/formulas/mathematics/college/shoblnof09hm9v8barp9lvjdvnnvb7tyjy.png)
Where P is the final value, P0 is the initial value, i is the interest rate, t is the time in years and n is a value that depends on the compound rate (let's assume that is monthly, so we have n = 12)
Calculating the principal (P0) for account A, using the interest (P - P0) equal 27, we have:
![\begin{gathered} P-P_0=P_0(1+(0.032)/(12))^(18)-P_0 \\ 12=P_0(1.00266667)^(18)-P_0 \\ 12=P_0(1.049-1) \\ P_0=244.90 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/q36wman2cebgssus2znx1wri7vj1bm4boh.png)
So the principal for account A is $244.90.
For account B, we have:
![\begin{gathered} 27=P_0(1+(0.024)/(12))^(27)-P_0_{} \\ 27=P_0(1.055-1) \\ P_0=490.91 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/kcbi59998l990ir522uw8x7f3m5f8fljlu.png)
The principal for account B is $490.91.